1997
DOI: 10.1046/j.1365-2826.1997.00550.x
|View full text |Cite
|
Sign up to set email alerts
|

Fos Expression by Naloxone in LHRH Neurons ofthe Mediobasal Hypothalamus and Effects of Pentobarbital Sodium in the Proestrous Rat

Abstract: Because Fos is thought to be induced in neurons that are activated, we examined whether luteinizing hormone-releasing hormone (LHRH) neurons expressed Fos protein when they were stimulated by an opioid receptor antagonist naloxone (NAL), expecting to identify LHRH neurons which are regulated by opioid neurons directly or indirectly. Further, we examined whether an ovulation-blocking dosage of pentobarbital sodium (PB) would affect the NAL-induced Fos expression. Female rats were infused with naloxone (5 mg/kg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 4 publications
(6 reference statements)
1
10
0
Order By: Relevance
“…They are thus consistent with the hypothesis that stimulation of pulsatile GnRH secretion by these agents involves a subset of GnRH neurons located in the MBH. Similar results have recently been reported in the rat, where naloxone has been shown to increase the percentage of GnRH cells expressing Fos in the lateral hypothalamic area, the most caudal portion of their distribution (38). While neural systems can be activated without concomitant Fos/FRA expression (37), the association of the two is sufficiently common that Fos/FRA expression is now generally accepted as an indication of an increase in neural activity (23,24).…”
Section: Discussionsupporting
confidence: 84%
“…They are thus consistent with the hypothesis that stimulation of pulsatile GnRH secretion by these agents involves a subset of GnRH neurons located in the MBH. Similar results have recently been reported in the rat, where naloxone has been shown to increase the percentage of GnRH cells expressing Fos in the lateral hypothalamic area, the most caudal portion of their distribution (38). While neural systems can be activated without concomitant Fos/FRA expression (37), the association of the two is sufficiently common that Fos/FRA expression is now generally accepted as an indication of an increase in neural activity (23,24).…”
Section: Discussionsupporting
confidence: 84%
“…Whether all of these hypophysiotropic GnRH neurons, or just a subpopulation, are involved in the pulsatile secretion of GnRH is unclear. Studies undertaken in rodents suggest that <100 GnRH neurons are sufficient for pulsatile LH secretion [25][26][27] and that the most caudally positioned GnRH neuron cell bodies might be preferentially involved in pulse generation 28,29 .…”
Section: Generation Of a Gnrh-lh Pulsementioning
confidence: 99%
“…Since it has been shown that a very small number of GnRH neurons, i.e., a total of about 20 neurons, in the mediobasal hypothalamus [73, 74, 75, 76, 77]generate pulsatile GnRH release [78, 79, 80, 81, 82], and only 10–20 neurons are able to produce volleys of multiunit activity, each revealing the GnRH secreting activity of the GnRH pulse generator [83], the activity of the majority of GnRH neurons, probably more than 400 neurons [77, 84], would be overlooked at least in ordinary culture conditions. Even so, it is necessary to more definitely differentiate two subgroups of GnRH neurons in our olfactory placode cultures.…”
Section: Discussionmentioning
confidence: 99%